ECONOMIC SECURITY OF UKRAINE THROUGH THE LENS OF INVESTMENT ATTRACTIVENESS AND GEOPOLITICAL RISKS - Пустовар, Владислав (SWorldJournal, 2025)
The article examines the current state of Ukraine’s investment environment under conditions of warfare and geopolitical instability. The author analyzes the impact of external and internal factors, including the war with Russia, corruption risks, legal in